2010
DOI: 10.1007/s00428-010-0964-y
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor is frequently expressed in HER2-positive, ER/PR-negative breast cancers

Abstract: The estrogen receptor (ER)/progesterone receptor (PR)-negative breast carcinomas (BCs) encompass three molecular subtypes: one with human epidermal growth factor receptor 2 (HER) overexpression, one normal like, and the triple negative. The androgen receptor (AR) is expressed in 70-90% of invasive BCs. The aim of our study is to detect the expression of AR in a series of ER/PR-negative BCs to ascertain if there is clinical significance in relation to BC molecular subtypes. A immunohistochemical study for all r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
80
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 51 publications
(81 reference statements)
18
80
0
2
Order By: Relevance
“…According to this theory, ER À tumors could also be stimulated via androgen activity, and depending on testosterone serum levels and AR positivity, either through EGFR or direct stimulation via androgen pathway (58). Another notable finding of our clinical meta-analysis is the worse prognostication conferred by AR positivity for women with HER2 þ ER À (Her2-enriched) disease, albeit the analysis included three studies with 358 patients (7,11,44). Similar findings have been reported, with AR positivity associated with worse clinical outcome among HER2 þ (7) as well as patients with HER2…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…According to this theory, ER À tumors could also be stimulated via androgen activity, and depending on testosterone serum levels and AR positivity, either through EGFR or direct stimulation via androgen pathway (58). Another notable finding of our clinical meta-analysis is the worse prognostication conferred by AR positivity for women with HER2 þ ER À (Her2-enriched) disease, albeit the analysis included three studies with 358 patients (7,11,44). Similar findings have been reported, with AR positivity associated with worse clinical outcome among HER2 þ (7) as well as patients with HER2…”
Section: Discussionsupporting
confidence: 77%
“…These studies indicate that the frequency of AR positivity differs between different breast cancer subtypes; the highest positivity observed in ER-positive tumors in up to 80%-90% (6)(7)(8)(9)(10) and the lowest in triple-negative (TN) tumours, in up to 30% (6,7,11). Of note, a phase II trial assessing enzalutamide in metastatic TNBC, reported AR positivity (defined as !1%) in 79% of 404 cases analyzed (12).…”
Section: Introductionmentioning
confidence: 96%
“…This local conversion of androgens into estrogens within breast tissue is likely to be a relevant physiologic mechanism especially with respect to the development of ER-responsive tumors which, as discussed above, may also include some fraction of tumors that do not express ER-alpha any longer at the time of their clinical manifestation. Almost all ER-positive tumors are also androgen receptor (AR) positive (40), however, and the same is true for a considerable proportion of ER-negative breast carcinomas (41). Furthermore, the ER-negative/PR-negative/AR-positive breast tumor Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of AR expression is usually associated with early onset, high grade tumors negative for ER, PR and HER2 (12). Although the lowest AR expression was observed in TN cancers (24), up to 30% of them were positive for AR (10,13,25). That's why it was suggested that AR could be a potential target in management of AR-positive TN breast cancers in future.…”
Section: Discussionmentioning
confidence: 99%